TEACHER PERCEPTIONS OF FOLLOWERSHIP VALUE ON GRADUATE STUDENTS OF VHS - Anggri Sekar Sari; Rina Setyaningsih (Universitas Sarjanawiyata Tamansiswa, 2018)
Research is motivated by the needs of good workers in the industrial world. This need can be known from the teacher's understanding of followership value in Vocational High School (VHS)Â graduate students. The purpose of this research is to know VHS teacher perception about followership value. The research method used descriptive quantitative. The subject of research is the headmaster and teacher for of VHS Catering Service in Yogyakarta. Determination of sample through purposive sampling counted 20 respondents. The validity test of 27 statements concerning instruments is declared valid. While all instruments are stated reliable with high reliability (0.803> 0.7). An average total score of 3.6 which means highly expected. These results explain teachers' perceptions, one of the followership values of VHS graduate students very well. It explains that teacher perception about the student, that student work attitude is in the follower style with the exemplary follower. The final outcome of the student is expected to become an exemplary worker after graduation.